Unveiling the role of ferroptosis in the progression from NAFLD to NASH: recent advances in mechanistic understanding - Yu, Qian; Song, Lixing (Frontiers in Endocrinology, 2024)
Non-alcoholic fatty liver disease (NAFLD) is a prevalent and significant global public health issue. Nonalcoholic steatohepatitis (NASH) represents an advanced stage of NAFLD in terms of pathology. However, the intricate mechanisms underlying the progression from NAFLD to NASH remain elusive. Ferroptosis, characterized by irondependent cell death and distinguished from other forms of cell death based on morphological, biochemical, and genetic criteria, has emerged as a potential participant with a pivotal role in driving NAFLD progression. Nevertheless, its precise mechanism remains poorly elucidated. In this review article, we comprehensively summarize the pathogenesis of NAFLD/NASH and ferroptosis while highlighting recent advances in understanding the mechanistic involvement of ferroptosis in NAFLD/NASH.